Extension of the DNA binding consensus of the chicken c-Myb and v-Myb proteins. - Weston, K (1992)
The chicken c-myb gene and the v-myb oncogene transduced by avian myeloblastosis virus (AMV) encode DNA binding transcription activators. The DNA binding domain of AMV v-Myb displays a number of amino acid changes relative to c-Myb; v-Myb proteins in which one or more of three crucial residues in the DNA binding domain are mutated to resemble the c-Myb sequence display altered transformation phenotypes. In order to establish whether the spectrum of DNA binding sites which AMV v-Myb can recognise is different from that seen by chicken c-Myb, a site selection protocol was used to derive consensus binding sequences for three variant Myb proteins made in vitro, and also using nuclear extract from the v-myb transformed cell line BM2. The results show that the original consensus binding site defined for v-Myb, YAA-CKG, can be extended to YAACKGHH, and that this new consensus holds for both v-Myb and chicken c-Myb.